2014
DOI: 10.13005/ojc/300443
|View full text |Cite
|
Sign up to set email alerts
|

NMR and NBO investigation of Dopamine properties in point view of Brain activities

Abstract: Dopamine dosage is the main reason for panic, fear as well as exhilaration. In this study, it has been shown that the electron negativity of Cl, Br and F ions plays an important role in binding of these ions to dopamine receptors. The nervous quartiles effective drugs have been calculated via NMR and NBO approach. Moreover, the HOMO-LUMO energy gap of dopamine and its halogenated derivatives have been calculated at the B3LYP/6-31G* level. These calculations are so important in order to investigate many other d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Such diseases include Parkinson’s disease (PD), resulting from improper or insufficient release of dopamine into the brain, and Schizophrenia disease (SD), resulting from the change in the level of dopamine in the body system. Decreasing dopamine activity in the human and animal bodies results in attention deficit hyperactivity disorder . Nowadays, the majority of the research on dopamine molecules is moving in the direction of developing a sensitive method to analyze dopamine for curing many related diseases, and that is why it is important to understand the reactivity, structure, and stability of the dopamine molecule. , Combined nuclear magnetic resonance (NMR) and density functional theory (DFT) studies give details about electrochemical properties of dopamine and its activity as a neurotransmitter . Neurotransmitters and their metabolites in the human body are all guided by the presence of well-functioning and active dopamine molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such diseases include Parkinson’s disease (PD), resulting from improper or insufficient release of dopamine into the brain, and Schizophrenia disease (SD), resulting from the change in the level of dopamine in the body system. Decreasing dopamine activity in the human and animal bodies results in attention deficit hyperactivity disorder . Nowadays, the majority of the research on dopamine molecules is moving in the direction of developing a sensitive method to analyze dopamine for curing many related diseases, and that is why it is important to understand the reactivity, structure, and stability of the dopamine molecule. , Combined nuclear magnetic resonance (NMR) and density functional theory (DFT) studies give details about electrochemical properties of dopamine and its activity as a neurotransmitter . Neurotransmitters and their metabolites in the human body are all guided by the presence of well-functioning and active dopamine molecules.…”
Section: Introductionmentioning
confidence: 99%
“… 4 − 7 Decreasing dopamine activity in the human and animal bodies results in attention deficit hyperactivity disorder. 8 Nowadays, the majority of the research on dopamine molecules is moving in the direction of developing a sensitive method to analyze dopamine for curing many related diseases, 9 11 and that is why it is important to understand the reactivity, structure, and stability of the dopamine molecule. 12 , 13 Combined nuclear magnetic resonance (NMR) and density functional theory (DFT) studies give details about electrochemical properties of dopamine and its activity as a neurotransmitter.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies about DA have been reported based on the following aspects: (1) on the basis of quantum chemistry methods, such as density functional theory (DFT), thermodynamic properties of DAH+ are calculated, including geometry optimization, vibration assignments, and total translational and rotational entropy; (2) deprotonation–protonation conformations of DA; and (3) methods to measure and mechanical properties of DA electrochemically oxidized in solution. However, little or no emphasis is laid on the nature of DAH+ and electromagnetic effects on DAH+. …”
Section: Introductionmentioning
confidence: 99%